A Cloud of Doves - Harcourt, Palma (London, United Kingdom : William Collins Sons & Co. Ltd, 1985)
Nearly injured in a terrorist bomb blast Alex Linden recognizes the voice of one of his fellow survivors as that of Klaus von Raven, a former Nazi who was supposed to be dead.
Keywords: DETECTIVE AND MYSTERY STORIES -- FICTION